ANALISIS FINANCIAL INDICATOR DAN BIAYA AGENSI MANAJERIAL SEBAGAI PREDIKSI FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Octaviana Dwiyacita Pujiastuti, 16.05.62.0029; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
The purpose of this research is to test and analyze the influence of financial indicator and managerial agency cost to financial distress at manufacturing company listed on the Indonesia Stock Exchange in the periode 2013-2016.While financial indicator use profitability, liquidity, leverage, sales growth, and operating capacity. The population in this study are all of the manufacturing companies listed on the Indonesia Stock Exchange and is continously published financial statements in the year 2013-2016. Based on purposive sampling method, samples obtained is 38 companies in the period 2013-2016 so obtain 152 observations. The criteria of financial distress in this study was measured by using interest coverage ratio. This study used logistic regression as a data analysis tool.The result of this research showed that profitability and sales growth have significant negative impact on the financial distress condition. This research failed to prove effect of liquidity, leverage, operating capacity, managerial agency cost of experiencing financialdistress.Keywords: profitability, liquidity, leverage, sales growth, operating capacity, managerial agency costs and financial distress